Assembly of Direct on Line (Dol) & Forward Reverse Circuit in Control Panel - Deitje Sofie Pongoh; Nathaniel L. Bijang; Ryan G.N Polii; Dewi .M. Paputungan; Septio .F. Kondolumang; Yodi .S. Ganta (Syntax Corporation Indonesia, 2025)
This article offers a discussion on how to perform Direct On Line (DOL) and Forward Reverse or Alternating Round circuits in a live control panel. It covers the basic concepts, working principles, and practical applications of these circuits in industrial and electrical systems. Additionally, this article explores the necessary preparations, including component selection, cable configuration, and safety considerations to ensure proper implementation. The journal is intended to provide readers with a deeper understanding by incorporating the latest research and discoveries in the field. Through detailed explanations and technical insights, it aims to improve practical knowledge and skills in designing, assembling, and troubleshooting DOL and Forward Reverse circuits. This research uses a qualitative method by using information and experiences of several people who are united in this journal. This article presents an in-depth discussion of the assembly and implementation of Direct On Line (DOL) and Forward Reverse circuits in the control panel. It covers the basic theory, practical applications, and importance of these circuits in industrial automation. The study emphasizes key aspects such as component selection, cable configuration, and safety measures to ensure efficient and safe installation. In addition, the results of experiments and case studies highlight the effectiveness of this circuit in optimizing motor control operations. These findings contribute to improving the technical knowledge and skills of engineers, students, and practitioners in the field of electricity